Optimization of Melt in Mouth Tablets of Palonosetron HCl using 32 Full Factorial Design - Kinjal P. Modi, Pawan A. Rai, Harsh J. Trivedi, Madhu Sharma, Kunal N. Patel (Journal of Applied Pharmaceutical Science, 2016)
Palonosetron HCl is a 5HT3 antagonist licensed for the prevention of acute chemotherapy-induced nausea and vomiting (CINV) associated with highly emetogenic chemotherapy agents (HEC) and the prevention of CINV associated with moderately emetogenic cancer chemotherapy (MEC). It has a substantially longer half-life (Approximately 40 h). So, it was plan to prepare melt in mouth tablet which could rapidly dissolved and absorbed which may produce rapid onset of action. Melt in mouth tablets were prepared by direct compression method using various superdisintegrants like Kyron T314 and Vivasol, and evaluated for pre compression and post compression parameters. A 32 full factorial design was applied systematically to optimize responses. The concentration of Kyron T314 (X1) and concentration of Vivasol (X2) were selected as independent variables and disintegration time (Y1) and wetting time (Y2) as dependent variables. The prepared tablets were evaluated for hardness, friability, disintegration time, wetting time, drug content and in vitro drug release. The results indicated that concentration of X1 and X2 significantly affected Y1 and Y2. Regression analysis and numerical optimization were performed to identify the best formulation. Similarity (f2) and dissimilarity (f1) study for optimized batch was also carried out. Batch P9 was found to be best batch with 10.43 s. disintegration time, 19.53 s. wetting time and 99.02% drug release in 30 min. There was no drastic change in the result of tablets of optimized batch at end of six month accelerated stability study.